Merjenje sil med potiskanjem in vlečenjem Al-palic - Cvahte, Peter (Kovine zlitine tehnologije, 1999)
A system for measurment of local loads during a combined extrusion-drawing of aluminium rods has been developed and installed on an O.C.N. machine which allows extrusion without applying a pointing process prior to deformation. In order to measure forces in the normal direction and to estimate pressure inside the die, four additional strain gauges have been applied on the prestressing ring. This allows determination of friction factors even in the case when the angle of the deformation zone is small. Measurements were performed for rods made from 2030 (ASTM) ally with 42 mm in diameter and stability of the process has been analysed. The results show that the drawing process during dynamic friction regime is stable and extrusion process turned out to be unstable.
Keywords: aluminij; aluminum; vlečenje; palice; sile; merjenje